2018
DOI: 10.1200/jgo.17.00160
|View full text |Cite
|
Sign up to set email alerts
|

Illness Understanding and End-of-Life Care Communication and Preferences for Patients With Advanced Cancer in South Africa

Abstract: PurposeThe understanding of patients with cancer of their condition and their wishes regarding care as they approach end of life (EoL) have been studied more in high-income countries than in low- and middle-income countries (LMICs).Patients and MethodsData were analyzed from a cohort study (N = 221) of patients with advanced cancer who were recruited from a palliative care center in Soweto, South Africa (LMIC), between May 2016 and June 2017. Patients were asked about their understanding of their illness, esti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
49
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 27 publications
(50 citation statements)
references
References 33 publications
0
49
0
1
Order By: Relevance
“…A previous study from our center reported that most patients (76.9%) would not want to know how long they had to live even if their doctors knew. 26 This finding highlights a further challenge to effective and appropriate communication about end-of-life preferences between health care providers, patients, and their families and may also affect illness understanding. Inadequate communication and subsequent inappropriate expectations could add to the emotional and physical burden on caregivers trying to cope with limited resources and result in hospitalization of the patient.…”
Section: Discussionmentioning
confidence: 99%
“…A previous study from our center reported that most patients (76.9%) would not want to know how long they had to live even if their doctors knew. 26 This finding highlights a further challenge to effective and appropriate communication about end-of-life preferences between health care providers, patients, and their families and may also affect illness understanding. Inadequate communication and subsequent inappropriate expectations could add to the emotional and physical burden on caregivers trying to cope with limited resources and result in hospitalization of the patient.…”
Section: Discussionmentioning
confidence: 99%
“…However, results from previous studies, the majority of which were conducted in developed countries, have limited applicability in LMICS [20,21]. There are no published studies evaluating the knowledge, attitude, or self-efficacy towards palliative care among Mongolian nurses, and little is known regarding their level of preparedness to deliver palliative care.…”
Section: Introductionmentioning
confidence: 99%
“…One study found only 1 in 50 Black South African women with breast cancer reported that their provider had talked to them about their prognosis. 16 Living with breast cancer often causes women varied physical, emotional, and psychological challenges due to enduring treatment, with some describing treatment as highly traumatizing and a period of severe emotional suffering. 3,17 Total mastectomy remains the most common surgical treatment today in South African public health services, despite breast conserving surgery being the surgical treatment of choice in high-resource settings.…”
Section: Introductionmentioning
confidence: 99%
“…One study found only 1 in 50 Black South African women with breast cancer reported that their provider had talked to them about their prognosis. 16 …”
Section: Introductionmentioning
confidence: 99%